„Męczeństwo św. Apolonii" z Głuchowa. Płaskorzeźba z kolekcji gotyckiej Muzeum Archidiecezjalnego w Poznaniu - Wajroch, Agnieszka (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
The late-medieval scene depicting the "Martyrdom of St. Apollonia" has been part of the col- lections of the Archdiocesan Museum in Poznań since 1998. Previously this work furnished the interior of the parish church in Głuchów near Kościan. Viewed against the backdrop of the pre- served monuments of art in Greater Poland, the scene remains a unique and puzzling work. The article presents the hitherto state of research of this object and refers to the fundamental theses of Brosig, Dettloff, Kamzowa and Białłowicz-Krygierowa pertaining to its iconography, composi- tion and possible prototypes. The theme of St. Apollonia's martyrdom is discussed as a common phenomenon in the art of the end of the 15th and the beginning of the 16th century, though rarely encountered in the rendering represented by the Głuchów sculpture. The author provides a detailed description of the object and its analysis in terms of iconography, composition, naturalistic elements, narrativity of the rendering and the depth of bas-relief in which it was executed. A series of charac- teristics linking the monument from Głuchów with works originating from southern Germany are indicated, especially its undeniable affinity to a print by Diirer.